The Uses of Shared Revenue - Nathan, Richard P. (Journal of Finance, 1975)
Richard P. Nathan, The Uses of Shared Revenue, The Journal of Finance, Vol. 30, No. 2, Papers and Proceedings of the Thirty-Third Annual Meeting of the American Finance Association, San Francisco, California, December 28-30, 1974 (May, 1975), pp. 557-565